Caracterização e estudo antimicrobiano in vitro de micro e nanofibras de PLA/PVP incorporadas com óleo de copaíba produzidas através da fiação por sopro em solução - Batista, Roberta Ferreti Bonan Dantas (2013)
Polymeric nanostructures can be produced by various techniques, including solution blow spinning (SBS), which can be used to produce micro and nanofibers at lower cost compared to other techniques. One of the most commonly used polymers for this purpose is poly (lactic acid) PLA, due to its biodegradability and biocompatibility. However, because of their hydrophobicity, lower degradation rate compared with other polyesters and low surface reactivity, considered unfavorable characteristics for biomedical use, PLA has been blended with other polymers. The aim of this study was to produce micro and nanofibers of PLA and PLA/polyvinylpyrrolidone (PVP) blends, in different proportions, using the SBS technique, with and without the addition of copaiba oil, herbal medicine with known antimicrobial activity. Produced mats were characterized by SEM, TGA, DSC, XRD, FTIR and contact angle. The in vitro antimicrobial activity was tested by agar diffusion. Results showed that, in all the proportions tested, produced blends were immiscible. The addition of PVP and copaiba oil led to a reduction in PLA crystallinity. The addition of PVP increased PLA hydrophilicity, reducing contact angle, unlike oil, that increased hydrophobicity. Fiber diameter was influenced by the addition of both PVP and oil. However, its morphology remained unchanged. Agar diffusion tests showed that all blends containing copaiba oil presented antimicrobial activity against Gram-positive Staphylococcus aureus. Moreover, this activity was proportional to both the increase of PVP amount in the blends and to a reduction in the crystalline structure of the blends. It can be concluded micro- and nanofibers of PLA and PLA/PVP blends with the addition of copaiba oil were successfully produced by the SBS technique. Moreover, these fibers have antimicrobial activity and can be potentially used as a drug delivery system in biomedical applications.